2019
DOI: 10.1161/jaha.118.010825
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Everyday Psychosocial Stressors Are Associated With Greater Impairments in Endothelial Function in Young Adults With Major Depressive Disorder

Abstract: Background Despite the epidemiological associations between psychological stress, depression, and increased cardiovascular disease risk, no studies have examined the relation between naturally occurring psychosocial stressors and directly measured microvascular function in adults with major depressive disorder ( MDD ). We tested the hypothesis that young adults with MDD exposed to everyday psychosocial stressors would exhibit more severe impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Fourteen otherwise healthy nonmedicated adults with MDD were screened; of these, 12 patients (8 women) met the inclusion criteria for study enrollment (Table 1). Three of these adults with MDD participated in previous studies in our laboratory (15,16). Twelve healthy adults (8 women) without any history of major psychiatric illness, also recruited from campus using standard recruitment strategies, served as the control group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen otherwise healthy nonmedicated adults with MDD were screened; of these, 12 patients (8 women) met the inclusion criteria for study enrollment (Table 1). Three of these adults with MDD participated in previous studies in our laboratory (15,16). Twelve healthy adults (8 women) without any history of major psychiatric illness, also recruited from campus using standard recruitment strategies, served as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve healthy adults (8 women) without any history of major psychiatric illness, also recruited from campus using standard recruitment strategies, served as the control group. All participants underwent the structured clinical Mini-International Neuropsychiatric Interview (41), and a diagnosis of MDD was confirmed by a psychiatrist according to DSM-5 criteria (15,16). Exclusion criteria included comorbid current psychiatric disorders (e.g., psychosis, schizophrenia, bipolar disorder, panic disorder, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A link between neurovascular dysfunction and MDD pathology is supported by studies assessing peripheral vascular endothelial dysfunction in patients with depressive symptoms. For instance, MDD is associated with greater impairments in vascular conductance as measured by endothelium-dependent dilatation (Greaney, Koffer, Saunders, Almeida & Alexander, 2019). Furthermore, a prospective study of subjects with various depressive disorders has shown a lower relative uptake ratio (RUR) of blood flow in the brachial artery of MDD patients in comparison with non-depressed controls (Lavoie, Pelletier, Arsenault, Dupuis & Bacon, 2010).…”
Section: Neurovascular Adaptations In Human Depressionmentioning
confidence: 99%
“…25 These JAMA Network Open | Cardiology shown to be associated with perceived stress in patients with cardiovascular disease. 26 To examine whether chronic stress was associated with mortality, independent of baseline depressive symptoms, we performed a secondary analysis that adjusted for baseline PHQ-8 score in the Cox proportional hazards regression model. To understand whether baseline stress moderated the association between chronic stress and mortality, we assessed the interaction between baseline stress and chronic stress toward the outcome of mortality.…”
Section: Discussionmentioning
confidence: 99%